2014
DOI: 10.1111/febs.12828
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A viral nucleoprotein interacts with cytoskeleton scaffolding protein α‐actinin‐4 for viral replication

Abstract: Influenza A virus (IAV), similar to other viruses, exploits the machinery of human host cells for its survival and replication. We identified a-actinin-4, a host cytoskeletal protein, as an interacting partner of IAV nucleoprotein (NP). We confirmed this interaction using co-immunoprecipitation studies, first in a coupled in vitro transcription-translation assay and then in cells either transiently co-expressing the two proteins or infected with whole IAV. Importantly, the NP-actinin-4 interaction was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 44 publications
4
39
0
Order By: Relevance
“…NP is a multi-functional protein of IAV, and several host factors were identified to interact with NP, and the interaction between NP and host factors exhibited its diverse role in viral life cycle [37][38][39][40][41][42]. The human anti-apoptosis protein clusterin (CLU) is targeted by NP to induced apoptosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…NP is a multi-functional protein of IAV, and several host factors were identified to interact with NP, and the interaction between NP and host factors exhibited its diverse role in viral life cycle [37][38][39][40][41][42]. The human anti-apoptosis protein clusterin (CLU) is targeted by NP to induced apoptosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…ACTN-4 is an actin-binding protein which has been described to play a key role in immune response regulation due to infection. It has been involved in the expression of genes encoding proinflammatory cytokines, chemokines and adhesion molecules [39][40][41]. In women with PTL, Romero et al [25] reported a higher presence of ACTN-4 in women with MIAC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is not surprising that a large number of host cellular factors have been identified as interacting partners of influenza viral proteins based on this technique. Hsp40, Clusterin, Karyopherin A, actinin-4 and actin are few examples of cellular interactors of viral NP identified using Y2H [45][46][47][48][49]. Similarly, M1 has been reported to interact with Annexin A6 and Cyclophilin A [50,51].…”
Section: Genome-wide Evidence Of Positive and Restrictive Factors Regmentioning
confidence: 99%
“…All viral components including vRNPs, Matrix protein M1, and envelope proteins HA, NA and M2, are transported to and assembled at the apical plasma membrane [28]. NP and M1 have been reported to be associated with host cytoskeleton protein such as actin and actinin-4 which indicates a possible role in vRNP translocation to the budding site [48,49,77]. In the screening carried out by Brass et al, depletion of COPI subunits led to reduced expression of HA on the plasma membrane of the host cell, thus indicating involvement of these proteins in transport of viral glycoproteins (NA and HA) to the cell surface.…”
Section: Viral Assembly and Buddingmentioning
confidence: 99%